Human Nmnat1 Promotes Autophagic Clearance of Amyloid Plaques in a Drosophila Model of Alzheimer’s Disease - Zhu, Yi; Lobato, Amanda G.; Zhai, R. Grace; Pinto, Milena (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by irreversible cognitive decline with limited therapeutic approaches. We characterized a Drosophila model of amyloid pathology that expresses human amyloid-beta precursor protein (APP695) and β-site APP cleaving enzyme (BACE) in the nervous system. Our model recapitulates in vivo the age-dependent accumulation of BACE-derived C-terminal fragment (CTF) and amyloid plaques in the brain, one of the key pathological hallmarks of AD. Using this model, we assessed the effects on plaque formation of Nicotinamide mononucleotide adenylyltransferase (Nmnat), an evolutionarily conserved nicotinamide adenine dinucleotide (NAD+) synthase involved in cellular metabolism and neuroprotection. We compared the effects of overexpression of Drosophila Nmnat (dNmnat), human Nmnat1 (hNmnat1), human Nmnat2 (hNmnat2), and human Nmnat3 (hNmnat3), and observed that hNmnat1 has the highest efficacy in reducing amyloid aggregation and APP-CTF accumulation. Interestingly, we demonstrated that overexpression of hNmnat1 reduces amyloid plaques by promoting autophagic clearance. Our findings uncover a role of hNmnat1 in amyloid clearance and suggest an exciting neuroprotective potential of hNmnat1 in amyloid pathology.